Răspuns :
a).3(x+1)+2x+3=2x+8+2x-1 c).x+2x+3x+4x+5=5³
3x+3+2x+3=2x+8+2x-1 10x+5=125
5x-2x-2x=-1+8-3-3 10x=125-5
x=1 10x=120⇒x=120/10=12
b).2x+7(x+1)+5=18+3x+6 d).2(x+1)+3(x+2)+4x+5=2³·5
2x+7x+7+5=18+3x+6 2x+2+3x+6+4x+5=8·5
9x-3x=6+18-5-7 9x=40-5-6-2
6x=12 9x=27
x=12/6=2 x=27/9=3
e).(1+2+3+4+5)x=x+2x+3x+4x+25
x+2x+3x+4x+5x=x+2x+3x+4x+25
15x-x-2x-3x-4x=25
5x=25
x=25/5=5
f).7x+3(x-2)+6=x+36 și așa mai departe ! sper că te-am ajutat.
7x+3x-6+6=x+36
10x-x=36-6+6
9x=36
x=36/9=4
3x+3+2x+3=2x+8+2x-1 10x+5=125
5x-2x-2x=-1+8-3-3 10x=125-5
x=1 10x=120⇒x=120/10=12
b).2x+7(x+1)+5=18+3x+6 d).2(x+1)+3(x+2)+4x+5=2³·5
2x+7x+7+5=18+3x+6 2x+2+3x+6+4x+5=8·5
9x-3x=6+18-5-7 9x=40-5-6-2
6x=12 9x=27
x=12/6=2 x=27/9=3
e).(1+2+3+4+5)x=x+2x+3x+4x+25
x+2x+3x+4x+5x=x+2x+3x+4x+25
15x-x-2x-3x-4x=25
5x=25
x=25/5=5
f).7x+3(x-2)+6=x+36 și așa mai departe ! sper că te-am ajutat.
7x+3x-6+6=x+36
10x-x=36-6+6
9x=36
x=36/9=4
a.3x+3+2x+3=4x+7 5x+6=4x+7 5x-4x=7-6 x=1
b.2x+7x+7+5=24+3x 9x+12=24+3x 9x-3x=24-12 6x=12 x=12/6 x=2
c.10x+5=125 10x=125-5 10x=120 x=120/10 x=12
d.2x+2+3x+6+4x+5=40 9x+13=40 9x=40-13 9x=27 x=27/9 x=3
e.x+2x+3x+4x+5x=10x+25 15x=10x+25 15x-10x=25 5x=25 x=5
f.7x+3x-6+6=x+36 9x=x+36 9x-x=36 8x=36 x=36/8 x=9/2
g.4x+10=4x+11 x=0
h. are solutii
i.10x-3=3 10x=6 x=6/10
b.2x+7x+7+5=24+3x 9x+12=24+3x 9x-3x=24-12 6x=12 x=12/6 x=2
c.10x+5=125 10x=125-5 10x=120 x=120/10 x=12
d.2x+2+3x+6+4x+5=40 9x+13=40 9x=40-13 9x=27 x=27/9 x=3
e.x+2x+3x+4x+5x=10x+25 15x=10x+25 15x-10x=25 5x=25 x=5
f.7x+3x-6+6=x+36 9x=x+36 9x-x=36 8x=36 x=36/8 x=9/2
g.4x+10=4x+11 x=0
h. are solutii
i.10x-3=3 10x=6 x=6/10